2011
DOI: 10.1002/lary.21399
|View full text |Cite
|
Sign up to set email alerts
|

Cortical representation sites of mimic movements after facial nerve reconstruction: A functional magnetic resonance imaging study

Abstract: Direct facial nerve repair (FNIG) leads to restoration of the original cortical activation. A cross nerve suture (HFA or HFJA) changes cortical activation and leads to different patterns of cortical activation during lip and tongue movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
1
14
0
2
Order By: Relevance
“…However, these findings are purely empirical and further studies are required to understand these phenomena. Functional MRI would be the ideal tool for this purpose and its application preoperatively and postoperatively could represent the next step in the evolution of our study …”
Section: Discussionmentioning
confidence: 99%
“…However, these findings are purely empirical and further studies are required to understand these phenomena. Functional MRI would be the ideal tool for this purpose and its application preoperatively and postoperatively could represent the next step in the evolution of our study …”
Section: Discussionmentioning
confidence: 99%
“…For this special situation, together with the small cortical area affected, only mild shifts of neighboring representation sites into the lip area can be expected. Bitter et al (2011) postulated that, changes in somatotopic representation of the face, lip and tongue should be present only in the motor cortex but not in the somatosensory cortex as the facial denervation affects only the motor output and not the somatosensory input. With this investigation, we demonstrated that both reorganization processes are associated.…”
Section: Figurementioning
confidence: 99%
“…Motor integration is increased, and functional motor integration mainly occurs in the hemisphere contralateral to the paralyzed side ( Barkhof et al, 2014 ; He et al, 2014 ; Zacà et al, 2014 ). With the gradual recovery of facial nerve function, the functional activities in the related brain regions also gradually recover to the normal level ( Rijntjes et al, 1997 ; Bitter et al, 2011 ; Wu et al, 2014 ). fMRI in the resting state (R-fMRI) is less demanding for patient cooperation than that during complex activation tasks ( Buxton, 2013 ; Conklin et al, 2014 ; Fovet et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%